Guideline Adherence and Hearing Outcomes of Sudden Sensorineural Hearing Loss in the Military Health System. Issue 5 (8th January 2020) - Hughes, Charlotte K; Ryan, Matthew T; Adams, Jason; Esquivel, Carlos R
Abstract: Introduction: The American Academy of Otolaryngology-Head and Neck Surgery Foundation clinical practice guideline (CPG) proposes several treatment recommendations regarding sudden sensorineural hearing loss (SSNHL). The treatments for this disorder have been controversial and remain varied. We sought to determine CPG adherence and hearing outcomes of SSNHL within the Military Health System (MHS). Materials and Methods: This was a retrospective case series with chart review of the MHS's electronic medical record. Patients with SSNHL ( n  = 112) were treated between March 1, 2012 and September 30, 2015. Clinical improvement was defined as a 20-dB improvement in pure tone averages or a 20% increase in word recognition scores. Results: Oral steroids were used in 63 (56%) patients, intratympanic (IT) steroids were utilized in 11 (10%) patients, and combination therapy was used in 38 (34%) patients. Average pure tone averages improvements with oral steroids, IT steroids, and combination therapy were 31.2 dB (95% CI, 24.4–38.0), 13.4 dB (95% CI, 0.4–29.6), and 17.3 dB (95% CI, 9.32–25.3), respectively. Average word recognition scores improvements with oral steroids, IT steroids, and combination therapy were 29.64% (95% CI, 19.5–39.7), 14.43% (95% CI, −8.32 to 45.3), and 18.48% (95% CI, 5.48–31.5), respectively. Clinical improvements with oral steroids, IT steroids, and combination therapy were 65, 46, and 50%, respectively. Conclusion: The MHS is uniquely positioned to evaluate adherence to CPGs on a national and international level given the robust and standardized electronic medical record. Areas identified for improvement include more timely initiation of treatment, standardization of IT steroid dosing, more accurate coding for diagnosis and treatment, and standardization of audiology evaluation.